Unequal itineraries for graduates: a typology of entrance into labour market - Marques, Ana Paula (2015)
In the transition from higher education to the labour market, the critical correspondence between qualification and first job, as well as precariousness and/ or unemployment experiences has been a crucial topic of understanding of labour market as one of the main facets of social and socio-economic insecurity and risks in contemporary European societies. In this paper we intend to contribute to the debate on unpredictable itineraries of professional integration of graduates from Higher Education which revels simultaneously and differently patterns of employability and professionalization segments. By mobilising some of the research outcomes of the projects lead by us, it is our purpose to cross contributions from the sociology of professions and employment in order to analyse the main social forms of entrance into labour markets. Based on the articulation of two axes, namely, social regulation and professional mobility, which are structured in a continuum in abstract terms, four “ideal-types” of social forms were defined: professional markets, internal markets, transitional markets and secondary markets (in neoclassic terms). In that sense, main exploratory analytic dimensions were mobilised on four levels: symbolic (recognition and the importance of academic title, identity and integration), cognitive (expertise and professional experience), social-political (dominant contractual status, market independency) and organizational (career/hierarchical position).